Evaluation of external doses from exposure to gamma sources in the soil using the MCNP code - Trabidou, G.; Stamatelatos, I. E.; Kritidis, P.; Florou, H. (HNPS Advances in Nuclear Physics, 2019)
Monte Carlo Neutron, Photon transport code (MCNP) was utilized to calculate the external dose from exposure to gamma emitting radionuclides on the ground. The results of the simulation were compared with the experimental data and the results of calculations performed using other analytical methods of estimating external doses from the ground and was found to be in a very good agreement.